Introduction (Scottish Historical and Archaeological Internet Reports, 2004)
This section outlines the circumstances of discovery and the nature of the work carried out which forms part of a larger project on quartz technology in Scottish prehistory. Archaeologists have tended to focus on associated activity areas rather than the quarry itself in contrast to this paper. The project aims reflect this. As part of the work a small assemblage of probable Bronze Age lithics was recovered along with small amounts of Iron Age pottery.